Low luminosity Type II supernovae - IV. SN 2020cxd and SN 2021aai, at the edges of the sub-luminous supernovae class - Valerin G; Pumo ML; Pastorello A; Reguitti A; Elias-Rosa N; Gútierrez CP; Kankare E; Fraser M; Mazzali PA; Howell DA; Kotak R; Galbany L; et al. (OXFORD UNIV PRESS, 2022)
Photometric and spectroscopic data for two Low Luminosity Type IIP Supernovae (LL SNe IIP) 2020cxd and 2021aai are presented. SN 2020cxd was discovered 2 d after explosion at an absolute magnitude of M-r = -14.02 +/- 0.21 mag, subsequently settling on a plateau which lasts for similar to 120 d. Through the luminosity of the late light curve tail, we infer a synthesized Ni-56 mass of (1.8 +/- 0.5) x 10(-3) M-circle dot. During the early evolutionary phases, optical spectra show a blue continuum (T > 8000 K) with broad Balmer lines displaying a P Cygni profile, while at later phases, Ca II, Fe II, Sc II, and Ba II lines dominate the spectra. Hydrodynamical modelling of the observables yields R similar or equal to 575 R-circle dot for the progenitor star, with M-ej = 7.5 M-circle dot and E similar or equal to 0.097 foe emitted during the explosion. This low-energy event originating from a low-mass progenitor star is compatible with both the explosion of a red supergiant (RSG) star and with an Electron Capture Supernova arising from a super asymptotic giant branch star. SN 2021aai reaches a maximum luminosity of M-r = -16.57 +/- 0.23 mag (correcting for A(V) = 1.92 mag), at the end of its remarkably long plateau (similar to 140 d). The estimated Ni-56 mass is (1.4 +/- 0.5) x 10(-2) M-circle dot. The expansion velocities are compatible with those of other LL SNe IIP (few 10(3) km s(-1)). The physical parameters obtained through hydrodynamical modelling are R similar or equal to 575 R-circle dot, M-ej = 15.5 M-circle dot, and E = 0.4 foe. SN 2021aai is therefore interpreted as the explosion of an RSG, with properties that bridge the class of LL SNe IIP with standard SN IIP events.